Shape memory polymer smart plaster for orthopaedic treatments. (1st November 2022) - Jeewantha, Janitha; Jayalath, Sandaruwan; Emmanuel, Chris; Herath, Madhubhashitha; Forster, Elizabeth; Islam, Mainul; Leng, Jinsong; Epaarachchi, Jayantha
Abstract: Shape memory polymer (SMP) is a smart material that can respond to external stimuli and recover its permanent shape after being programmed. Researchers have been interested in SMPs for invasive biomedical applications, but there are many opportunities for non-invasive applications. Thus, in this study, a novel hybrid SMP nanocomposite smart plaster (SP) is synthesised for non-invasive orthopaedic fractured bone immobilisation. Due to its considerable structural properties, the SP for this study was synthesised with Bisphenol A epoxy, reinforced with E-glass fibres, its bioinspiration qualities were improved incorporating TiO2 nanoparticles. After that, the SP was preserved for three months under five different conditions. This was done to compare their environmental durability and usability for fractured bone immobilisation by analysing the resulting thermomechanical and shape memory properties. In addition, an Abaqus finite element model was developed and validated which can be used to optimise the design and geometrical parameters of the SP. The SP vitro performance was verified, demonstrating a lower limb leg cylindrical cast in less than 10 min. The SP at 50 °C and two layers of cotton webril produced the optimum results, and the recorded maximum undercast temperature was less than 45 °C, which was within the safe limit for human use. Furthermore, the undercast pressure did not surpass 30.2 ± 5.2 mmHg, indicating that the results are equivalent to other bone immobilisation procedures. Therefore, the synthesised SP showed a promising approach to address existing orthopaedic fractured bone limb immobilisation challenges.